Structured advice provided by a dietitian increases adherence of consumers to diet and lifestyle changes and lowers blood low‐density lipoprotein (LDL)‐cholesterol: the Increasing Adherence of Consumers to Diet & Lifestyle Changes to Lower (LDL) Cholesterol (ACT) randomised controlled trial. Issue 2 (11th September 2017) - Sialvera, T. E.; Papadopoulou, A.; Efstathiou, S. P.; Trautwein, E. A.; Ras, R. T.; Kollia, N.; Farajian, P.; Goumas, G.; Dimakopoulos, I.; Papavasiliou, K.; Koutsouri, A.; Zampelas, A.
Abstract: Background: Evidence from healthcare professionals suggest that consumer compliance to healthy diet and lifestyle changes is often poor. The present study investigated the effect of advice provided by a physician or dietitian on consumer adherence to these measures combined with consuming foods with added plant sterols (PS) with the aim of lowering low‐density lipoprotein cholesterol (LDL‐C). Methods: One hundred mildly‐to‐moderately hypercholesterolaemic individuals were enrolled into a parallel, randomised, placebo‐controlled study. Dietitians (dietitian group; DG) advised 50 individuals in six weekly face‐to‐face behavioural therapy sessions, whereas the other 50 received standard advice from physicians (physician group, PG). Both groups consumed foods with added PS (three servings a day) for 6 weeks. Subsequently, all individuals were followed‐up for another 6 weeks under real‐life conditions. Blood lipids were measured at baseline and weeks 6 and 12 and 3‐day diet diaries were taken at weeks 1, 6 and 12. Results: Individuals in the DG significantly improved their dietary habits, physical activity and increased PS intake compared to the PG. After 6 weeks, LDL‐C decreased in both groups compared to baseline without any significant differences between groups. At week 12, LDL‐C was further significantly improved only in the DG ( P = 0.006) compared to week 6. Total cholesterol, LDL‐C and triglycerides were significantly lower in the DG compared to the PG at week 12 after adjusting for levels at week 6 ( P < 0.001, P < 0.001 and P = 0.009, respectively). Conclusions: Although structured counselling by dietitians and common standard advice by physicians were equally effective with respect to improving blood cholesterol after 6 weeks, dietitians were more effective in the longer‐term (i.e. 6 weeks after the end of the intervention period).